The Effect Of Self Efficacy And Learning Motivation On Learning Outcomes With Learning Independence As Moderating Variables In Class StudentsXI-Accounting | Journal Of Global Research Publications - Loviana Uli Manurung; Choms Gary Ganda Tua Sibarani; Andri Zainal; Rini Herliani; Pasca Dwi Putra (Journal Of Global Research Publications, 2026)
The problem in this study is that Accounting Learning Outcomes have not met expectations in the 11th grade Accounting students of SMK Negeri 1 Patumbak. This study aims to determine the effect of Self-Efficacy and Learning Motivation on Learning Outcomes, with Learning Independence as a moderating variable, in 11th grade students at SMK Negeri 1 Patumbak. This research was conducted at SMK Negeri 1 Patumbak, located at Jl. Ujung Defense, Lantasan Baru, Patumbak District, Deli Serdang Regency, North Sumatra. This study used an ex post facto approach. The population was 35 11th grade Accounting students. The sample size was 35 students, using total sampling. Data collection was conducted through documentation and questionnaire distribution. The questionnaire was first tested for validity and reliability. The collected data was then processed using multiple linear regression with SPSS version 30 software. The results of this study indicate that: (1) Self-efficacy has a positive and significant effect on students' accounting learning outcomes. This is indicated by a regression coefficient of 0.321 with a significance level of 0.021, which is less than 0.05. (2) Learning motivation has a positive and significant effect on students' accounting learning outcomes. The analysis results show a regression coefficient of 0.428 with a significance level of 0.004, which is less than 0.05. (3) Self-efficacy and learning motivation simultaneously have a significant effect on students' accounting learning outcomes. This is proven by a calculated F-value of 18.672 with a significance level of 0.000, which is less than 0.05. (4) Learning independence moderates the effect of self-efficacy on accounting learning outcomes. This is indicated by the significance value of the interaction variable between self-efficacy and learning independence of 0.043, which is less than 0.05. (5) Learning independence moderates the influence of learning motivation on accounting learning outcomes. The analysis results show a significance value of the interaction variable between learning motivation and learning independence of 0.029, which is less than 0.05. This means that learning independence strengthens the influence of learning motivation on students' accounting learning outcomes